(untitled) (Journal of Nepal Physical Society, 2022)
We compared the structural and optical properties of the gold films deposited on copper substrates by the traditional fire-gilding method and electroplating method which are being adopted by the craftsmen in the Kathmandu valley, Nepal. Atomic force microscopy (AFM) and reflectance spectroscopy were employed to characterize the surface morphology and optical reflectance of the samples, respectively. In the AFM images of the surface of the gold films, we observed that the surfaces of the fire-gilded films not only are smoother but also have higher reflectance than that of the electroplated gold films. In the corrosion experiment by chemical etching of the gold films, fire-gilded samples showed superior corrosion resistance than electroplated gold films.